2006
DOI: 10.14310/horm.2002.11196
|View full text |Cite
|
Sign up to set email alerts
|

Papillary thyroid carcinoma producing granulocyte-macrophage colony-stimulating factor is associated with neutrophilia and eosinophilia

Abstract: thyroid tumors producing colony-stimulating factors associated with neutrophilia and/or eosinophilia are very rare and almost all of them concern anaplastic thyroid cancer. Only one case of papillary thyroid carcinoma associated with neutrophilia and one case of medullary thyroid carcinoma associated with eosinophilia have been reported. In this report a 72-year old male patient with metastatic papillary thyroid carcinoma associated with neutrophilia and eosinophilia is described. While investigating the cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…It has been speculated that neutrophilia could develop as a result of ectopic production of myeloid growth factors as part of a paraneoplastic syndrome or a nonspecific response to cancer-associated inflammation secondary to tissue destruction and cytokine releases [13,19]. Initially, higher NLR and PLR values versus the healthy controls may show the cancer-related inflammation in our RAI and non-RAI group.…”
Section: Discussionmentioning
confidence: 88%
“…It has been speculated that neutrophilia could develop as a result of ectopic production of myeloid growth factors as part of a paraneoplastic syndrome or a nonspecific response to cancer-associated inflammation secondary to tissue destruction and cytokine releases [13,19]. Initially, higher NLR and PLR values versus the healthy controls may show the cancer-related inflammation in our RAI and non-RAI group.…”
Section: Discussionmentioning
confidence: 88%
“…Polymorphonuclear leukocytes can infiltrate the tumour and can be large in number near the necrotic regions83; some tumours have a prominent eosinophilic leukocytic infiltrate in areas that are not necrotic; tissue culture studies indicate that these types of anaplastic carcinomas can secrete an eosinophil chemotactic factor 90…”
Section: Anaplastic Carcinoma (Undifferentiated Carcinoma)mentioning
confidence: 99%
“…Most G-CSFeproducing tumors are poorly differentiated and are likely to develop distant metastases. 8,11,12,[14][15][16][17][19][20][21][22] G-CSF stimulated the growth of a nonhematopoietic malignant cell line in vivo, 28 and G-CSF was also considered to be a major autocrine growth factor in rapid tumor proliferation and metastasis. 29 It has also been suggested that G-CSF has a priming effect on platelet aggregation and thrombin generation and subsequently induces a hypercoagulable state.…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition, G-CSF can be used to mobilize hematopoietic stem cells from healthy donors to harvest stem cells for transplantation. 7 Several G-CSFeproducing malignant tumors have been reported in the lung, [8][9][10][11] urinary bladder, 12,13 digestive organs, [14][15][16][17][18][19] and thyroid gland, [20][21][22] but not in the breast. We present a rare case of a G-CSFeproducing spindle cell carcinoma of the left breast.…”
Section: Introductionmentioning
confidence: 99%